Incomplete Cervical Dilation with Fetal Mummification in Goat: A Case Report - Warghat, Chinmay; poornima, Poornima Dwivedi; sahu, uttam kumar; Rele, Gauri; Sushil, Sushil Kumar (Animal Reproduction Update, 2024)
The current case details the successful management of dystocia in a goat due to incomplete cervical dilation and fetal mummification. The ‘Referral Veterinary Polyclinic’, ICAR-IVRI, Izatnagar received the animal, which had a history of brownish-red vaginal discharge and straining for 5 h. Per-vaginal examination revealed a fetal mass lodged in the reproductive tract with incomplete cervical dilation. Induction therapy was administered to facilitate cervical dilation, allowing for the manual extraction of the mummified fetus. After three days of postoperative treatment, the goat recovered without complications.